Cytotoxicity and genotoxicity of coronaridine from Tabernaemontana catharinensis A.DC in a human laryngeal epithelial carcinoma cell line (Hep-2) - Walace Fraga Rizo; Luis Eduardo Ferreira; Vanessa Colnaghi; Juliana Simões Martins; Leonardo Pereira Franchi; Catarina Satie Takahashi; Rene Oliveira Beleboni; Mozart Marins; Paulo Sérgio Pereira; Ana Lúcia Fachin (Genetics and Molecular Biology, 2013)
Cancer has become a major public health problem worldwide and the number of deaths due to this disease is increasing almost exponentially. In the constant search for new treatments, natural products of plant origin have provided a variety of new compounds to be explored as antitumor agents. Tabernaemontana catharinensis is a medicinal plant that produces alkaloids with expressive antitumor activity, such as heyneanine, coronaridine and voacangine. The aim of present study was firstly to screen the cytotoxic activity of the indole alkaloids heyneanine, coronaridine and voacangine against HeLa (human cervix tumor), 3T3 (normal mouse embryo fibroblasts), Hep-2 (human laryngeal epithelial carcinoma) and B-16 (murine skin) cell lines by MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide); and secondly to analyze the apoptotic activity, cell membrane damage and genotoxicity of the compound that showed the best cytotoxic activity against the tumor cell lines tested. Coronaridine was the one that exhibited greater cytotoxic activity in the laryngeal carcinoma cell line Hep-2 (IC50 = 54.47 µg/mL) than the other alkaloids tested (voacangine IC50 = 159.33 µg/mL, and heyneanine IC50 = 689.45 µg/mL). Coronaridine induced apoptosis in cell lines 3T3 and Hep-2, even at high concentrations. The evaluation of genotoxicity by comet assay showed further that coronaridine caused minimal DNA damage in the Hep-2 tumor cell line, and the LDH test showed that it did not affect the plasma membrane. These results suggest that further investigation of coronaridine as an antitumor agent has merit.